2020
DOI: 10.3390/ani10010085
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic Neoplasia in the Intact and Castrated Dog: How Dangerous is Castration?

Abstract: Elective gonadectomy in the dog is a topic of interest for clinicians, pet-owners, and society. Although canine prostatic neoplasia (CPN) has a low incidence (0.35%), reports of an increased risk for castrated dogs attract attention and cause concern in pet-owners. Our aim is to provide professionals and non-professionals with a detailed description of this possible side effect of gonadectomy in the dog. The mean age at diagnosis of CPN ranges from 8.5 to 11.2 years. Medium to large size breeds are more freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 75 publications
0
34
0
Order By: Relevance
“…Prostatic enlargement is a non-specific abnormality which may be caused by a variety of inflammatory, non-neoplastic and neoplastic diseases ( 9 , 17 , 18 ). Considering that only a small percentage of dogs with a non-malignant disorder are castrated ( 19 ), while neutering status might represent a risk factor for prostate cancer ( 9 , 19 , 20 ), prostatic enlargement in castrated dogs should be regarded as suspicious for malignancy and therefore evaluated carefully ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prostatic enlargement is a non-specific abnormality which may be caused by a variety of inflammatory, non-neoplastic and neoplastic diseases ( 9 , 17 , 18 ). Considering that only a small percentage of dogs with a non-malignant disorder are castrated ( 19 ), while neutering status might represent a risk factor for prostate cancer ( 9 , 19 , 20 ), prostatic enlargement in castrated dogs should be regarded as suspicious for malignancy and therefore evaluated carefully ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…If a diagnosis was listed in the record as "suspected, " the case was excluded from the analysis for that specific disease. Prostate cancer in males, sometimes considered as comparable to mammary cancer, was not tracked because of the low incidence-−0.35% (14). If the cancer did occur more frequently, it would have been interesting to follow because the cancer tends to increase in incidence with neutering (14).…”
Section: Study Parametersmentioning
confidence: 99%
“…In the last two decades, several studies have shown a statistically significant increased risk of diagnosis of various neoplastic diseases in neutered males and females compared to intact dogs, which has sparked an international debate on whether elective neutering is still a tool that should be routinely performed [ 9 , 10 ]. However, a definitive explanation of how the absence of gonadal hormones may influence the development of neoplasia in reproductive or nonreproductive tissues is still pending [ 11 ].…”
Section: Introductionmentioning
confidence: 99%